Passive Design Strategies in Bolon House through Activity Pattern and Wind Environment - Yusuf Ariyanto; Kosuke Nakano; Yen-Khang Nguyen-Tran (Institute of Research and Community Outreach, Petra Christian University, Indonesia, 2026)
In the Bolon house, a traditional Toba Batak vernacular architecture, the spatial layout is organized according to cultural meanings assigned to each zone, reflecting the social structure and adapting to the regional climate through passive strategies. Since scientific verification of such a principle remains limited, this research evaluates the thermal comfort within the Bolon house, focusing on the relationship between wind environment and local activity patterns. Firstly, the routine activities of residents were recorded and categorized into the activity pattern. Secondly, the thermal comfort range was calculated using the CBE Tool for two representative seasonal dates, while wind environments were analyzed through CFD simulations. Findings show that wind speeds are generally low, with a slight increase in the western rear zone due to the prevailing East wind. Nevertheless, indoor comfort is maintained during most activities, particularly in the central communal zone, which consistently provides the most suitable conditions for daily life.